PENGARUH MEDIA BUKU DONGENG TERHADAP NILAI PROFIL PANCASILA DIMENSI BERAKHLAK MULIA SISWA KELAS 4 SD IU FADLUN NAFIS BANGSRI - Ismail, Akbaruddin; Attalina, Syailin Nichla Choirin; Hamidaturrohmah, Hamidaturrohmah (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
This study aims to investigate the effect of using fairy tale books as a learning medium on the values of the noble character dimension in the Pancasila Student Profile among fourth-grade students at SD Islam Unggulan Fadlun Nafis Bangsri. The research is grounded in the urgency of character education within the Merdeka Curriculum and the need for contextual and engaging learning strategies. The study applied a quantitative approach using a pre-experimental design: One Group Pretest-Posttest Design involving 26 students. Data were collected using a Likert-scale questionnaire based on five indicators of noble character and analyzed using descriptive statistics, normality and homogeneity tests, and paired sample t-test. The results showed an increase in mean scores from 68.46 (pretest) to 80.04 (posttest). The t-test yielded a significance value of p < 0.001 and a Cohen's d score of 3.431, indicating a very large effect size. These findings suggest that fairy tale books are effective in enhancing students' character values, particularly in the moral-spiritual dimension. Story-based learning helps students internalize moral values through engaging, reflective, and age-appropriate narratives. This research recommends the integration of fairy tale books as a character education strategy within the implementation of the Pancasila Student Profile in elementary schools. ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh penggunaan media buku dongeng terhadap nilai dimensi berakhlak mulia dalam Profil Pelajar Pancasila siswa kelas IV SD Islam Unggulan Fadlun Nafis Bangsri. Latar belakang penelitian ini didasarkan pada pentingnya pendidikan karakter dalam Kurikulum Merdeka, serta perlunya pendekatan pembelajaran yang kontekstual dan menyenangkan. Penelitian menggunakan pendekatan kuantitatif dengan desain pre- experiment tipe One Group Pretest-Posttest Design pada 26 siswa. Instrumen yang digunakan adalah angket skala Likert dengan lima indikator dimensi akhlak mulia. Data dianalisis menggunakan uji statistik deskriptif, uji normalitas, uji homogenitas, dan paired sample t-test. Hasil penelitian menunjukkan adanya peningkatan skor rata-rata dari 68,46 (pretest) menjadi 80,04 (posttest). Uji t menghasilkan nilai signifikansi (p < 0,001) dan nilai Cohen’s d sebesar 3,431 yang tergolong dalam efek sangat besar. Hal ini membuktikan bahwa media buku dongeng efektif dalam meningkatkan nilai karakter siswa, khususnya pada aspek akhlak mulia. Penggunaan buku dongeng terbukti mampu membantu internalisasi nilai-nilai karakter melalui narasi yang menarik, reflektif, dan kontekstual. Penelitian ini merekomendasikan pemanfaatan buku dongeng sebagai strategi pembelajaran karakter dalam implementasi Profil Pelajar Pancasila di sekolah dasar.